Social responsibility, an essential strategic option for a sustainable development in the field of bio-economy - Armenia Androniceanu (Amfiteatru Economic Journal, 2019)
Globalization determines the economic environment to identify new development models that harmoniously integrate the modern digital economy with corporate social responsibility for sustainable development. The aim of the research was to discover the main ways to increase corporate social responsibility in Romanian organizations in 3 key sub-areas of bio-economy. We also sought to identify and analyze the implementation level of fundamental principles and values of corporate social responsibility, strategic priorities and methods used by Romanian companies in the target group to strengthen it. Another objective of the research was to develop a hierarchy of strategic (economic, social and environmental) interests of the top managers of the analyzed organizations, reflecting the new business philosophy. The research tools used were: an online questionnaire, a semi-structured interview with general managers and document analysis, that is: 10 organizational strategies, 60 bi-annual reports on corporate social responsibility and 30 budget executions from the last three years of activity of the organizations involved in the research. The data obtained were correlated and processed in Excel and SPSS. The novelty of the research consists in taking a systemic approach, from a managerial point of view, of corporate social responsibility in the field of bio-economy being the first applied research of its kind on the segment of medium-sized companies from three representative sub-domains of Romanian bio-economy.
Keywords: O13; P16; Q57; 330; corporate social responsibility (CSR); bio-economy; sustainable development; strategic interests